Enhancing 21st Century Skills through Role-Playing in Economics Classrooms: A Quasi-Experimental Study - Dwi Gustin, Mandasari; Endra, Priawasana; Aliyah, Suhartatik; Widjiati, Widjiati (Journal of Education Technology and Inovation, 2025)
The integration of 21st-century skills into economics education is essential to prepare students for complex global challenges. This quasi-experimental study examined the effectiveness of role-playing pedagogy in enhancing critical thinking, collaboration, and communication skills among senior high school students in Jember, Indonesia. A total of 160 eleventh-grade students participated, divided into an experimental group (n = 80) receiving role-playing instruction and a control group (n = 80) taught through traditional lectures. Data were collected using validated rubrics and analyzed with SPSS 26.0, employing independent samples t-tests and ANCOVA with pretest scores as covariates. Results revealed that the experimental group significantly outperformed the control group across all measured domains, with large effect sizes (Cohen’s d > 1.0). Specifically, role-playing was found to foster deeper cognitive engagement, collaborative interactions, and effective communication within simulated economic contexts. These findings confirm the pedagogical potential of role-playing as a transformative instructional strategy that aligns with experiential and constructivist learning theories. The study contributes to the growing evidence base advocating for active learning approaches in secondary education and highlights the importance of embedding authentic, simulation-based activities into economics curricula. Implications for practice suggest that integrating role-playing can enhance both academic outcomes and transversal competencies, equipping students with critical skills necessary for future academic and professional success